Tinjauan Etika Bisnis Islam dalam Penggunaan Timbangan Sembako Dalam Jual Beli (Studi Kasus di pasar Mendahara Ilir, Tanjabtim) - Ambok Pangiuk (Indonesian Journal of Islamic Economics and Business, 2019)
The purpose of this study is to explore and analyze the awareness of sellers and shop owners in using weights correctly and honestly based on Islamic business ethics. Taxonomy, Domein, and component methods are used as a qualitative method to explore and analyze the sample of focus. The sampling method is purposive sampling they are sellers or shops. owners that have practices selling in Mehdahara Ilir Market more than 4 years. Triangulation model from buyer and seller is used to confirm the result from the previous method. The result shows that most of the seller understand the concept of honest but don’t understand the concept of Islamic business ethics. The weights used are traditional weights, with no standard its effects to different confirmatory weight from buyer, and made the lack of trustworthy. the research suggests the government gives them the standard weights and socialization its important to get trust and loyalty from the customer.